LEGAL DEVELOPMENT AND URGENCY OF PERSONAL DATA PROTECTION IN INDONESIA - Ngompat, Yohanes Leonardus; Mary Grace Megumi Maran (JILPR Journal Indonesia Law and Policy Review, 2024)
This research aims to know and analyze the development of personal data protection law and to know and analyze the urgency of personal data protection in Indonesia. This research is normative juridical research using secondary data. The approaches used are legislative and historical approaches. The data collected is then analyzed qualitatively. Based on the results of the research, it is known that the laws and regulations on personal data protection continue to develop from time to time. The regulation begins with the inclusion of Article 28 G Paragraph (1) in the 1945 Constitution which becomes the legal basis in guaranteeing the rights of every person or owner of personal data and reaches the peak where a special regulation has been formed that specifically regulates the protection of personal data, namely in Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). Previously, the regulation on personal data protection was regulated partially and sectorally, so with the enactment of the PDP Law, there is a special regulation related to personal data protection. In relation to the urgency of personal data protection, personal data is important to protect because along with the development of technology and information, it is easier for violations to occur, including the misuse of personal data. Violations of personal data should be prevented and handled seriously because personal data is very important data related to one's privacy. Protection of personal data can ultimately increase public confidence in providing personal data to support government policies in fulfilling public interests without violating people's personal rights.